An efficient and selective conversion of sorbitol in ionic liquids: Use of ion exchange resin as a solid acid catalyst. Issue 37 (13th September 2017) - Kamimura, Akio; Murata, Kengo; Kawamoto, Takuji
Graphical abstract: Highlights: Efficient conversion of sorbitol to isosorbide in hydrophobic ionic liquids. Microwave heating achieved very rapid conversion. Perfect separation of product from ionic liquids and catalyst was accomplished by simple extraction manipulation. Abstract: Sorbitol was readily converted by heating in hydrophobic ionic liquids by the presence of ion exchange resins. Chemoseletivity of the dehydration depended on the choice of ion exchange resin; Nafion selectively produced isosorbide while Amberlite gave 1, 5-anhydrosorbitol along with unreacted sorbitol. Ionic liquids used in the reaction were readily recovered by simple extraction procedure. With these procedures, we succeeded to prepare isosorbide in pure form, not contaminated with either ionic liquids or acid catalyst, by simple experimental procedure.